F-Chart Method For Design Domestic Hot Water Heating System In Ayer Keroh Melaka - Mohd Rosli, Mohd Afzanizam; Mohd Zaki, Danial Shafiq; Abdul Rahman, Fatiha; Sepeai, Suhaila; Abdul Hamid, Nurfaizey; Nawam, Muhammad Zaid (Penerbit Akademia Baru, 2019)
Renewable energy is an alternative approach of energy supply that meets the needs of the present generations without compromising the ability of future generations to meet their own needs. One type of renewable energy is solar energy. Solar energy systems convert solar energy into useful energy. In designing a solar collector, there are predictable and unpredictable parameters that are considered. Predictable parameters include performance characteristics of collector and mainly concern weather data such as solar radiation, ambient temperature, wind speed, direction, and other parameters is performance characteristics of collectors. This work analysed the use of the f-chart method in design liquid solar heating systems due to its simplicity and ability to estimate the fraction of total heating load supplied by the solar heating system. This method is very commonly used in designing for both active and passive solar heating systems, especially in selecting sizes and type of solar collectors that provide the hot water and heating loads. In this research, the data of the project is analysed to calculate based on the f-chart graph. The results show that the area in Melaka around the vicinity of Ayer Keroh is suitable for the installation of the flat-plate solar collector. The total annual heating load of domestic hot water in Melaka is 9.55 GJ and the annual fraction of the load supplied by solar energy is 78.42% which is suitable for implementation and installation in Ayer Keroh, Melaka